APPLICATION OF THERMAL IMAGING IN FORENSIC VISION - Nigam, Ranjeet Kumar (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2018)
The thermal imaging camera is a new emerging tool in forensic visionary technology for seeing in total darkness and takes an image of heat radiation from an object in diverse weather condition like rain, fog and smoke etc. The normal close circuit television (CCTV) cameras are blinded by the sun resulting they do not see too much in total darkness. All objects, regardless of temperature, emit some level of energy. IR cameras have the unique ability to capture this information and display it in a thermal image to be viewed and analyzed. This paper describes some of science behind this technology and its application.